VISUAL AND GRAPHIC TOOLS FOR EFFECTIVE COMMUNICATION IN THE CONTEXT OF THE VALUES OF CHINA’S BELT AND ROAD INTERNATIONAL INITIATIVE - Yuan, P.; Krotova , T. (Art and Design, 2023)
Purpose: To study the role of branding and design elements in the effective communication of the values of the Belt and Road Initiative (BRI). Methodology: The methods of observation, comparison, synthesis and generalization have been used to analyze the existing branding and design elements within the initiative, as well as to review official documents. Methods of formal, stylistic, compositional, and coloristic analysis have been used to analyze visual designs used by companies and organizations associated with the BRI. Results: The article analyzes the latest research that helps to determine the methods of using images, typography and color to effectively represent the cooperation and inclusiveness associated with the BRI, to implement successful communication of BRI values and promote the goals of the initiative. The features of the use of maps and networks, compasses, flags, and landmarks of transport infrastructure for communication within the BRI values are considered. The key design features that are often used in the visual media of BRI branding are identified. These include objects of communication and cooperation (maps, roads, and railways), as well as objects that symbolize the values of the cultures of the participating countries (flags, landmarks). It has been found that blue and gold colors are often used to denote stability and success in branding elements. Scientific novelty: Previous studies have focused mainly on the economic and political implications of BRI. Instead, the present study is the first to analyze branding and design elements in terms of communication effectiveness and their use to effectively communicate BRI values to a global audience. In addition, the study provides ideas for developing branding components for international development projects. Practical significance. This study has a number of practical implications for organizations and governments involved in BRI initiatives. The results of the study can be used to develop more effective branding and communication strategies to communicate the value of BRI to a global audience.